(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
This article discusses the philosophical ideology advocated and promoted by the academic, anthropologist and politician, Dr WWM Eiselen, during different periods of history in South Africa. The central focus is on the ideology that influenced his academic writings and the consequent influence of this academic knowledge on government theory and practice. The need to preserve Bantu institutions and the emphasis of language to promote ethnic culture were central aspects of his political project has been demonstrated. Further it is pointed out that these recurring themes had a significant influence on the crafting of education for Bantu people. In conclusion Eiselen’s pronouncements and writings, which were underpinned by his philosophical and political theories, should be understood in terms of what was happening at that particular period in South Africa’s history.